A Meyers type regularity result for approximations of second order elliptic operators by P1 finite elements. Issue 5 (8th October 2013) - Badr, Nadine; Russ, Emmanuel
<x xml:space="preserve">Abstract</x> We prove a Meyers type regularity estimate for approximate solutions of second order elliptic equations obtained by P1 finite elements. The proofs rely on interpolation results for Sobolev spaces on graphs. Estimates for second order elliptic operators on rather general graphs are also obtained.